Exploring the Underlying Message of Kalbe Farma’s Corporate Social Responsibility (CSR) Strategy: Video Water Supply for Watuagung - Mirana Hanathasia; M. Kresna Noer; Annisa Fitriana Lestari (Research Synergy Foundation, 2024)
Watuagung is an area in Indonesia that is experiencing water shortage. The lack of water caused some conflicts in the village. People fought to get clean water. In 2013, a local hero strived for water supply for the village. Moreover, now, water is easy to find in Watuagung village. Therefore, the quality of life of the people is getting better. Because of the water supply, people can harvest plants and earn money. This village achievement occurred with the involvement of Kalbe Farma, Indonesia’s pharmaceutical company, in its CSR program. Furthermore, this CSR journey is described in the short video